2023
DOI: 10.1186/s40164-023-00410-5
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota as a booster for radiotherapy: novel insights into radio-protection and radiation injury

Abstract: Approximately 60–80% of cancer patients treated with abdominopelvic radiotherapy suffer post-radiotherapy toxicities including radiation enteropathy and myelosuppression. Effective preventive and therapeutic strategies are lacking for such radiation injury. The gut microbiota holds high investigational value for deepening our understanding of the pathogenesis of radiation injury, especially radiation enteropathy which resembles inflammatory bowel disease pathophysiology and for facilitating personalized medici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 90 publications
1
5
0
Order By: Relevance
“…The microbiome studies shape oncologic outcomes and are now being leveraged for the development of novel personalised therapeutic approaches in anticancer treatment. However, this topic exceeds the scope of this paper and has been addressed elsewhere (Chrysostomou et al, 2023 ; Yi et al, 2023 ).…”
Section: Other Factorsmentioning
confidence: 86%
“…The microbiome studies shape oncologic outcomes and are now being leveraged for the development of novel personalised therapeutic approaches in anticancer treatment. However, this topic exceeds the scope of this paper and has been addressed elsewhere (Chrysostomou et al, 2023 ; Yi et al, 2023 ).…”
Section: Other Factorsmentioning
confidence: 86%
“…Conversely, a disrupted microbiota has the potential to diminish the effectiveness of radiotherapy (10) . Most of these observations were made concerning the gut microflora, which directly affects the functioning of the immune system (36,37) . Matson et al, based on studies conducted on mice, observed that gut microflora can also migrate to other closely related tissues and influence cancer progression (38) .…”
Section: Discussionmentioning
confidence: 99%
“…This bacterium is commercially available as a probiotic, but its increase in abundance in trauma patients who have died suggests a potential negative effect ( 51 ). Similarly, there are mixed reports on the role that A. muciniphila plays following radiation ( 23 , 42 , 50 , 52 , 53 ). Tian et al ( 52 ) used an oral gavage of Akkermansia to demonstrate increases in mouse survival over a 30-day period following irradiation with enhanced production of SCFAs.…”
Section: Discussionmentioning
confidence: 99%
“…Tian et al ( 52 ) used an oral gavage of Akkermansia to demonstrate increases in mouse survival over a 30-day period following irradiation with enhanced production of SCFAs. Conversely, Akkermansia has been associated with inflammation as it is consistently found as an organism more abundant following irradiation and in colitis models ( 42 , 50 , 52 54 ). Gerassy-Vainberg et al ( 50 ) demonstrated that radiation induces a proinflammatory state with increased Akkermansia .…”
Section: Discussionmentioning
confidence: 99%